The Effect of Electronic Customer Relationship Management (E-CRM) on Customer Loyalty Through Customer Experience on WhatsApp Loyalty Recipients - Sanjaya, Harry; Astuti, Miguna; Noraini Nasirun; Yudi Nur Supriadi (Dinasti Publisher, 2025)
This study aims to analyze the impact of Electronic Customer Relationship Management (E-CRM) on customer loyalty through customer experience among users of the WhatsApp Loyalty YOBO platform in the Food and Beverage (F&B) sector. The research seeks to answer the following questions: (1) Does E-CRM influence customer experience, (2) Does customer experience impact customer loyalty, and (3) Does customer experience mediate the relationship between E-CRM and customer loyalty. A quantitative explanatory research design was employed, with data collected through structured questionnaires from 360 respondents who were WhatsApp Loyalty YOBO users. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4.0 to evaluate the relationships between E-CRM, customer experience, and customer loyalty. Validity, reliability, and mediation analyses were conducted to ensure robust results. The study found that E-CRM significantly enhances customer experience, which, in turn, positively influences customer loyalty. Furthermore, customer experience was identified as a mediating variable that strengthens the relationship between E-CRM and customer loyalty. These results highlight the importance of customer experience in maximizing the benefits of E-CRM tools. Differences in the impact were observed across demographic groups, indicating the potential for tailored strategies. The findings demonstrate the pivotal role of E-CRM in fostering customer loyalty by enhancing customer experience. Businesses in the F&B industry are encouraged to optimize E-CRM features like personalization, timely communication, and seamless service delivery. Future research can explore additional factors, such as market competition or cultural influences, to further elucidate E-CRM's role in driving customer loyalty. Keyword: customer experience, customer loyalty, digital marketing, E-CRM, WhatsApp Loyalty.